2009
DOI: 10.1002/bem.20487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weak combined static and extremely low‐frequency alternating magnetic fields on tumor growth in mice inoculated with the Ehrlich ascites carcinoma

Abstract: It has been shown that the ultralow-frequency extremely weak alternating component of combined magnetic fields (MFs) exhibits a marked antitumor activity. The parameters of this component have been found (frequency 1, 4.4, 16.5 Hz or the sum of these frequencies; intensity 300, 100, 150-300 nT, respectively) at which this MF in combination with a collinear static MF of 42 microT inhibits or suppresses the growth of Ehrlich ascites carcinoma (EAC) in mice. It was shown that the exposure of mice with EAC to comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 16 publications
(14 reference statements)
4
27
0
1
Order By: Relevance
“…Strikingly, electromagnetic fields seemed to be most effective in their inhibition of cancer cell growth at moderate and at low intensity. Novikov et al exposed a total of 1750 BALB/c mice to alternating fields at frequencies ranging from 0.5 to 16.5 Hz and intensities from 100 to 300 nT [67]. Mice were intraperitoneally injected with 1 × 106 Ehrlich ascites cancer cells, which caused zero survival of control group animals within 13-18 days.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, electromagnetic fields seemed to be most effective in their inhibition of cancer cell growth at moderate and at low intensity. Novikov et al exposed a total of 1750 BALB/c mice to alternating fields at frequencies ranging from 0.5 to 16.5 Hz and intensities from 100 to 300 nT [67]. Mice were intraperitoneally injected with 1 × 106 Ehrlich ascites cancer cells, which caused zero survival of control group animals within 13-18 days.…”
Section: Resultsmentioning
confidence: 99%
“…A synergistic effect was found when immunocompetent mice bearing murine Lewis lung carcinomas (LLCs) or B16 melanotic melanomas treated with cisplatin were exposed to extremely low-frequency (ELF)-MFs (2). Novikov et al (3) suggested that MFs have a marked antitumor activity. Mice with transplanted Ehrlich ascites carcinoma (EAC) were exposed to weak MFs and the tumor tissue was almost completely absent after exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Además, se muestran los valores medidos de resistencia e inductancia para cada par de bobinas Helmholtz. Considerando aplicaciones de generación de campo magnético de baja magnitud y frecuencia (Novikov et al, 2009) en el orden del campo geomagnético cuya magnitud dependiendo de la ubicación geográfica oscila entre 25 µT y 65 µT (Martino et al, 2010b), se define un rango de generación de +200 µT para cada componente de campo magnético B z , B y , y B x ; es decir, que la corriente máxima de operación para cada par de bobinas será 1.5 A, 1.45 A y 1.4 A respectivamente. Este sistema permite la generación de campos magnéticos estáticos y variantes en el tiempo (formas de onda senoidal, cuadrada y triangular), teniendo en cuenta que la frecuencia máxima de operación es de 100 Hz.…”
Section: Parámetros Nominalesunclassified